2017
DOI: 10.1007/s00192-017-3441-1
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle activity during impact activities in continent and incontinent women: a systematic review

Abstract: The findings of this systematic review suggest that impact activities causing involuntary and reflex PFM activity should be the subject of further study. This may help guide clinical studies to improve our understanding of how the PFMs react during impact activities and to determine best practices that can be included in rehabilitation programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 49 publications
0
27
1
3
Order By: Relevance
“…In another study of 16 healthy women, EMG activity during jumps occurring while drop landing and mini-trampolining was above that of the PFM onset threshold and pre-and co-contraction activity increased significantly with jumping height and body weight force [45]. A review of 28 studies about PFM activity during impact activities, concluded that the timing of PFM activity in relation to the activity of other trunk muscles appears to be important in maintaining continence and that women with SUI have delayed PFM activity during impact activities [46].…”
Section: How Does Exercise Affect Pfm Activity?mentioning
confidence: 99%
“…In another study of 16 healthy women, EMG activity during jumps occurring while drop landing and mini-trampolining was above that of the PFM onset threshold and pre-and co-contraction activity increased significantly with jumping height and body weight force [45]. A review of 28 studies about PFM activity during impact activities, concluded that the timing of PFM activity in relation to the activity of other trunk muscles appears to be important in maintaining continence and that women with SUI have delayed PFM activity during impact activities [46].…”
Section: How Does Exercise Affect Pfm Activity?mentioning
confidence: 99%
“…De fato, existem diferentes fabricantes de transceptores de sinal de EMG com diferentes padrões de transmissão, software de analise e compatibilidade [28]. Assim, pesquisas que objetivam aferir o AP com EMG precisam se adaptar às restrições dos produtos do mercado, implicando em mais custos ou limitações nas análises devido aos softwares impostos pelos fabricantes como nos trabalhos de Park [23], Luginbuehl [14] e Moser [18] O sistema foi avaliado através de critérios pré estabelecidos para o hardware e para o software. Separar a avaliação do software da avaliação do hardware foi uma solução encontrada para acelerar o processo de prototipagem, permitindo entregar os subsistemas separadamente para análise.…”
Section: Trabalhos Relacionadosunclassified
“…18 In a systematic review on electromyographic PFM activity during impact activities such as coughing, running on a treadmill, horseback riding, and rapid arm movements, the authors found that nonpregnant women with stress UI had delayed PFM activity. 19 The authors concluded that impact activities causing involuntary and reflex PFM activity needs further study. Bø 3 proposed in one of the hypotheses about how exercise may affect the PFM, that a feed-forward loop or cocontractions of the PFM during increase in intraabdominal pressure may strengthen the PFM.…”
Section: Commentmentioning
confidence: 99%